WEALTH, POVERTY AND ECONOMIC INEQUALITY: A CHRISTIAN VIRTUE RESPONSE - Ward, Kate (Asian Horizons, 2016)
This dissertation argues that both wealth and poverty function as moral luck to impede the pursuit of virtue and that economic inequality worsens the problem.